Application of grading evaluation method of water radioactivity level in Chongqing section of Yangtze River. (May 2022) - Hu, Shijie; Lin, Xuefeng; Yang, Qiang; Du, Hengyan; Zhao, Xue; Chen, Rui; Li, Guang
Abstract: The major rivers in a region are usually vital sources of drinking water for local populations, and the concentration of radionuclides in the water is intimately tied to people's health. The varying concentration limits set by the World Health Organization are appropriate as screening values for determining the pollution of water sources, but their capacities as regulatory or early warning limits are restricted. In daily management, the regulatory authority needs to manage water bodies by level based on the concentration of radionuclide to indicate the potential pollution risks. From 2017 to 2019, a statistical analysis and dosage evaluation were conducted on the water radioactivity level in the Chongqing section of the Yangtze River in this study. The Modified Nemerow Index method based on the dose conversion coefficients was applied for the grading evaluation of the water radioactivity level, allowing the grading effect discussed. The results showed that the concentration of radionuclides in the Chongqing section of the Yangtze River and its contribution to the annual effective dose of the human body were lower than the limits stated in the Guidelines for Drinking Water Quality (Fourth Edition) . And the samples in the section were 52.94% in Grade Ⅰand 47.06% in Grade Ⅱ, meaning few potential radioactive pollution risks exist there. Compared with other methods. The Modified Nemerow Index method combines the Traditional Nemerow Index method with the dose conversion coefficient of nuclides making it more realistic for the early warning and control of radioactive pollution in water bodies, which is worth popularizing and implementing. Graphical abstract: Image 1 Highlights: The method for predicting potential radioactive contamination with low concentrations of radionuclides. Discuss the application of soil heavy metal pollution grading evaluation method in the evaluation of water bodies. Proposing to use the dose conversion coefficients of radionuclides to assign weight in the MNI method.